Comparative systematic review of low-cost adsorbents for fluoride and heavy metal removal in rural water supplies in South Africa (1 January 2000 – 30 June 2025) - Fagbohun, Temitope R.; Okechukwu, Viola O.; Adelusi, Oluwasola A.; Okonkwo, Jonathan O. (Frontiers in Environmental Science, 2025)
IntroductionAccess to safe drinking water remains a critical challenge in rural developing regions, including South Africa, where naturally occurring fluoride and anthropogenic heavy metals (Pb2+, Cd2+, As, Cr6+) pose significant public health risks. Low-cost adsorbents derived from agricultural and natural materials have emerged as a promising solution for decentralized water treatment in resource-limited areas.MethodsThis systematic review was conducted following PRISMA 2020 guidelines and registered in PROSPERO (CRD420251084775). A total of 29 studies published between 2008 and 2025 were included. Eligible studies investigated the use of low-cost adsorbents—such as biochar, activated carbon, bone char, clay minerals, and agricultural residues—for the removal of fluoride and heavy metals from water sources. Key variables extracted included removal efficiency, adsorption capacity, operational conditions, and regeneration potential.ResultsAcross the 29 studies, most adsorbents achieved removal efficiencies exceeding 90% for Pb2+, Cd2+, and Cr6+, with adsorption capacities ranging from 10 to >200 mg/g. Biochar and activated carbon demonstrated the highest performance, including superior regeneration potential, while agricultural by-products and clays contributed significant affordability and accessibility advantages. Approximately 40% of the included studies validated adsorbent performance using pilot- or field-scale testing, with slightly reduced but still effective removal compared to laboratory findings.Discussion/ConclusionFindings confirm that low-cost adsorbents offer practical, sustainable, and scalable treatment options for rural water contamination in South Africa. However, gaps remain in long-term regeneration, field durability, and treatment of emerging contaminants such as pharmaceuticals and microplastics. The review highlights the importance of context-specific, low‐cost technologies for advancing water security and supporting public health. Overall, the evidence promotes the adoption of locally sourced adsorbents as viable technologies for improving rural water supply management in South Africa.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251084775, CRD420251084775